3D-4D visualisation of IoT data from Singapore's National Science Experiment. Issue 1 (2nd January 2022) - Benita, Francisco; Perhac, Jan; Tunçer, Bige; Burkhard, Remo; Schubiger, Simon
ABSTRACT: This paper introduces Singapore Views as a novel 3D-4D interface to visualize large space-time datasets with applications in smart cities. The engine enables a combination of geographic information system, geo-located data with high-resolution 3D models and multimedia. Space-time datasets from Singapore's National Science Experiment (NSE) 2016 are used to test the functionality of Singapore Views. The findings from the user study revealed the new visualization engine was helpful in extracting insights from space-time data. Finally, this study also contributes to the current discussion of how to visualize knowledge thereby support the planning of smart cities.